ANALISIS KUALITAS KOMPOS DARI CAMPURAN PAKIS-PAKISAN DAN KOTORAN AYAM MENGGUNAKANLIMBAH CAIR PABRIK MINYAK KELAPA SAWIT DAN EM-4 SEBAGAI AKTIVATOR - M. Zulfikri; Amir Awaluddin; Itnawita ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Ferns weed is a plant that is widely available in the oil palm plantation that grows as a parasite on the trunks of palm oil and will result in decreased quality of fresh fruit bunches, These ferns can be used as compost material because it contains enough nutrients.The composting process is done by adding chicken manure and effective microorganism (EM-4) as well as liquid waste palm oil mill (LCPMKS) as an activator.Analysis of compost quality is determined by the parameters water content, pH and C/N ratio for 30 days and analyzed every 5 days composting time.The results showed that the addition of EM-4 activator on kompostidak mixture gives a real difference to the control sample on the value of C / N ratio with a P value> 0.05The compost produced memliliki pH value, water content and C/N ratio, respectively for 8, 40-52% dan17-19 after 30 days of composting time.